2020
DOI: 10.1186/s41021-020-00165-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of smoking cessation on biological monitoring markers in urine

Abstract: Introduction Urinary nicotine and cotinine levels are often measured as biomarkers for tobacco smoke exposure. However, these biomarkers are not appropriate to evaluate the effects of quitting smoking for several days, because of their short half-lives. In this study, we focused on the changes in the urinary 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL) levels of 55 patients in a smoking cessation program, because of the long half-life. At the same time, urinary 7-methylguanine (m7Gua) and 8-hydroxy-2′-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…In this work, we detected levels of 8-OHdG in umbilical blood and plasma similar as reported by other authors [52][53][54], who employed the same methodology. In addition, we found signi cantly lower 8-OHdG levels in the smoking women group, consistent with previously reported ndings [55,56]. However, the 8-OHdG levels were signi cantly lower in the new-borns of the smoking women, contrary to the report of Ebina et al, where the 8-OHdG levels of the new-borns of smoking women were high.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this work, we detected levels of 8-OHdG in umbilical blood and plasma similar as reported by other authors [52][53][54], who employed the same methodology. In addition, we found signi cantly lower 8-OHdG levels in the smoking women group, consistent with previously reported ndings [55,56]. However, the 8-OHdG levels were signi cantly lower in the new-borns of the smoking women, contrary to the report of Ebina et al, where the 8-OHdG levels of the new-borns of smoking women were high.…”
Section: Discussionsupporting
confidence: 91%
“…However, the 8-OHdG levels were signi cantly lower in the new-borns of the smoking women, contrary to the report of Ebina et al, where the 8-OHdG levels of the new-borns of smoking women were high. Nevertheless, they did not specify the time of smoking during pregnancy [52], which is important since 8-OHdG higher levels have been observed in active adult smoker [57,58] than in pregnant women [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of tobacco exposure biomarkers. We determined the urinary nicotine, cotinine, 3-HC, and NNAL levels according to the method of Kawasaki et al (31) with slight modifications. Briefly, 500 μl aliquots of the urine samples were thawed and mixed with 500 μl of 50 mmol acetate buffer (pH 4.0), followed by the addition of 2 μl of dl-cotinine (methyl-D 3 ) and NNAL (1,2',3',4',5',6'-13 C 6 ) stock solutions as internal standards.…”
Section: Study Participantsmentioning
confidence: 99%
“…Other MS conditions were the same as previously reported. (31) Analysis of DNA damage biomarkers. Urinary m 7 Gua and 8-OHdG concentrations were determined by the previously described method.…”
Section: Study Participantsmentioning
confidence: 99%
“…12 In addition, a recent longitudinal study has revealed a decrease in urinary 8-OHdG levels by smoking cessation. 13 Previous studies also reported the negative correlation between body mass index (BMI) and urinary 8-OHdG levels. 8,11 The mechanism remains unclear, although obesity is a risk factor for lifestyle-related diseases.…”
mentioning
confidence: 96%